2021
DOI: 10.4269/ajtmh.20-0757
|View full text |Cite
|
Sign up to set email alerts
|

A Computational Modeling Study of COVID-19 in Bangladesh

Abstract: The COVID-19 pandemic has spread globally. Only three cases in Bangladesh were reported on March 8, 2020. Here, we aim to predict the epidemic progression for 1 year under different scenarios in Bangladesh. We extracted the number of daily confirmed cases from March 8 to July 20, 2020. We considered the suspected-infected-removed (SIR) model and performed a maximum likelihood-based grid search to determine the removal rate (ɣ). The transmission was modeled as a stochastic random walk process, and sequential Mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 15 publications
1
4
0
Order By: Relevance
“…Our results are similar to previously reported R 0 in China [ 17 , 27 ] and neighboring country India [ 28 ]. After a week of nation-wide lockdown, R t decreased substantially from early April 2020 in Bangladesh, which corroborates with those of [ 29 , 30 ]. Our finding suggests that Bangladesh has seen an upheaval of R t in early February 2021, which corroborates with Abbott et al [ 31 ].…”
Section: Discussionsupporting
confidence: 84%
“…Our results are similar to previously reported R 0 in China [ 17 , 27 ] and neighboring country India [ 28 ]. After a week of nation-wide lockdown, R t decreased substantially from early April 2020 in Bangladesh, which corroborates with those of [ 29 , 30 ]. Our finding suggests that Bangladesh has seen an upheaval of R t in early February 2021, which corroborates with Abbott et al [ 31 ].…”
Section: Discussionsupporting
confidence: 84%
“…Some studies have revealed how multiple variables contribute to the spread of the virus, 26 but with the inclusion of proper interventions, the spread of COVID-19 can be monitored. 27 However, it should be mentioned that this forecast is strongly related to the past pattern. The current situation in India represents a declining trend in daily reported infections.…”
Section: Resultsmentioning
confidence: 98%
“… 11 Moreover, studies have shown that the increase in COVID-19 cases is due to a country’s poor governance, increased corruption, inadequate healthcare facilities, and weak public health communication. 12 , 13 The COVID-19 pandemic has tested healthcare systems and their structure for emergency responsiveness through their supply-chain response and high demand for ICU beds. 14 Thus far, many models of governance have shown poor response, especially in rural areas where the emergency support system has suffered severely with a shortage of medical supplies and poor treatment levels.…”
Section: Introductionmentioning
confidence: 99%